Implementasi BIM pada Struktur Gedung Laboratorium Terpadu Universitas Samudra Menggunakan Software Revit - Anwar, Ahmad; Alamsyah, Wan; Purwandito, Meilandy (Journal of Applied Civil Engineering and Infrastructure Technology, 2025)
This research applied three working methods, namely 3D modeling, quantity take-off (QTO), and bar bending schedule (BBS). The main objective of this research was to compare the calculation results of the conventional method with the Building Information Modeling (BIM) method in the construction of the Samudra University Integrated Laboratory Building. The implementation of BIM showed significant differences compared to the conventional approach, especially in 3D visual output and cost estimation (5D). The application of BIM facilitated more accurate 3D modeling and faster and more efficient cost estimation. In addition, BIM also improved the construction inspection process as it allowed the checking of work items without the need for manual inspection one by one. The QTO results using BIM (Revit Student Version) show a difference in calculation volume compared to the conventional method. In the concrete work, there had been a difference of 23.27 m³ or 2.08%, while in the screw reinforcement work, there had been a difference of 9,597.69 kg or 10.33%. For plain reinforcement, there had been a difference of 3,497.28 kg or 3.86%, and the total weight of reinforcement had been 13,094.96 kg or 7.14%.